Ending the neglect of global oral health: time for radical action - Watt, Richard; Daly, Blánaid; Allison, Paul; Macpherson, Lorna M D; Venturelli, Renato; Listl, Stefan; Weyant, Robert J; Mathur, Manu R; Guarnizo-Herreño, Carol C; Celeste, Roger Keller; Peres, Marco A; Kearns, Cristin; et al. (The lancet, 2019)
Oral diseases are a major global public health problem affecting over 3·5 billion people. However, dentistry has so far been unable to tackle this problem. A fundamentally different approach is now needed. In this second of two papers in a Series on oral health, we present a critique of dentistry, highlighting its key limitations and the urgent need for system reform. In high-income countries, the current treatment-dominated, increasingly high-technology, interventionist, and specialised approach is not tackling the underlying causes of disease and is not addressing inequalities in oral health. In low-income and middle-income countries (LMICs), the limitations of so-called westernised dentistry are at their most acute; dentistry is often unavailable, unaffordable, and inappropriate for the majority of these populations, but particularly the rural poor. Rather than being isolated and separated from the mainstream health-care system, dentistry needs to be more integrated, in particular with primary care services. The global drive for universal health coverage provides an ideal opportunity for this integration. Dental care systems should focus more on promoting and maintaining oral health and achieving greater oral health equity. Sugar, alcohol, and tobacco consumption, and their underlying social and commercial determinants, are common risk factors shared with a range of other non-communicable diseases (NCDs). Coherent and comprehensive regulation and legislation are needed to tackle these shared risk factors. In this Series paper, we focus on the need to reduce sugar consumption and describe how this can be achieved through the adoption of a range of upstream policies designed to combat the corporate strategies used by the global sugar industry to promote sugar consumption and profits. At present, the sugar industry is influencing dental research, oral health policy, and professional organisations through its well developed corporate strategies. The development of clearer and more transparent conflict of interest policies and procedures to limit and clarify the influence of the sugar industry on research, policy, and practice is needed. Combating the commercial determinants of oral diseases and other NCDs should be a major policy priority.
Gesehen am 22.04.2020